The Political Complexity of Coastal Flood Risk Reduction: Lessons for Climate Adaptation Public Works in the U.S. - D. J. Rasmussen; Robert E. Kopp; Rachael Shwom; Michael Oppenheimer (Earth's Future, 2021)
Abstract Coastal climate adaptation public works, such as storm surge barriers and levees, are central elements of several current proposals to limit damages from coastal storms and sea‐level rise in the United States. Academic analysis of these public works projects is dominated by technocratic and engineering‐driven frameworks. However, social conflict, laws, political incentives, governance structures, and other political factors have played pivotal roles in determining the fate of government‐led coastal flood risk reduction efforts. Here, we review the ways in which politics has enabled or hindered the conception, design, and implementation of coastal risk reduction projects in the U.S. We draw from the literature in natural hazards, infrastructure, political science, and climate adaptation and give supporting examples. Overall, we find that (1) multiple floods are often needed to elicit earnest planning; (2) strong and continuous leadership from elected officials is necessary to advance projects; (3) stakeholder participation during the design stage has improved outcomes; (4) legal challenges to procedural and substantive shortcomings under environmental protection statutes present an enduring obstacle to implementing megastructure proposals.